The Challenges in Translating Indonesian Abstract Text to English - Jumiati Jumiati; Godefridus Bali G (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2020)
The translation is a tool to communicate for people who have different languages. The translation makes it easier for them to understand what others say and get more information from the other languages, especially on the abstract that will help the researcher so that it is easy to get the desired information. In the abstract, their much information that gains for the researcher. Therefore, the researcher is dedicated to studying the challenges of translating. This study aims to know the challenges in translating Indonesian abstract text to English faced by eight-semester students' of the English Department at Widya Gama Mahakam Samarinda. The subject used of the study was 8th-semester students in the English department of Widya Gama Mahakam Samarinda. There are five students as participants. The research design to use is qualitative. To collect the data, the researcher uses interview guidelines. The interview result showed that lexicon, grammar, element semantic, and translation style were the challenges in translating Indonesian abstract text to English.